Identifying robust predictors of treatment response in trauma-affected refugees: Results from a randomised controlled trial - Jessica Carlsson; Maja Bruhn; Ida Sophie Poschmann; Derrick Silove; Maria Lurenda Westergaard; Erik Lykke Mortensen; Hinuga Sandahl (PLoS ONE, 2025)
Background Given the high prevalence of trauma-related mental health problems in a growing population of refugees, identifying robust predictors of treatment outcome can optimize treatment strategies and resource allocation. The current study aimed to examine the robustness of predictors from seven previous predictor studies at the Competence Centre for Transcultural Psychiatry (CTP). Methods We studied if predictors from previous studies could be replicated in a sample of 219 refugees with PTSD who participated in a new distinct study conducted at CTP. We included all variables previously found to be significantly related to treatment response, as measured via the Harvard Trauma Questionnaire (HTQ) and the Hamilton Depression Scale (HAM-D). We categorised the variables as sociodemographic factors, CTP predictor index items, and baseline assessment scores. We performed regression analyses with one exposure variable at a time, controlling for baseline assessment scores corresponding to the dependent variable. We also conducted multiple linear regression analyses to examine the variance explained in total by the identified significant predictor variables. Results The study successfully replicated several predictors of treatment response for PTSD and depression, including a high understanding of therapy concepts, acceptability of psychological treatment, ability to reflect, motivation for active participation and cognitive resources, as well as low baseline pain levels. The findings replicated a U-shaped relationship between age and treatment response for depression, indicating better outcomes for younger participants and those over 60. Multiple regression analyses explained 28% and 39% of the variance in the PTSD (HTQ) and depression (HAM-D) treatment responses, respectively. Conclusions This study contributes to the understanding of treatment response predictors in trauma-affected refugees by replicating findings from previous research in a new sample. It highlights the importance of modifiable factors, such as psychotherapy readiness, and underscores the necessity for tailored interventions to enhance treatment efficacy. As the global refugee crisis grows, the insights from this research can inform mental health strategies, ultimately improving care for this vulnerable population. Future research should continue to investigate modifiable predictors to further enhance treatment outcomes. Trial registration ClinicalTrials.gov NCT02761161